On the Price and Volume Effects from Green Certificates in the Energy Market - Torstein Bye (Statistics Norway, Research Department, 2003)
We present a model for an energy market that includes a green certificate for suppliers of energy from renewables and a purchaser commitment to buy these certificates. We show that price and volume effects in the energy market are ambigous under a wide range of alternative levels of the purchaser commitment. We calibrate our model to data for the Norwegian economy. Simulations shows a downward movement in energy prices as the government starts increasing the level of the purchaser commitment. This implies that the producer of ordinary energy pays for the restriction in the market while energy consumption and consumer surplus increases. When the purchaser commitment increases above a certain level, the purchaser price increases and the volume effect is negative. Although the effects are sensitive to elasticities of demand and supply of both technologies, the main results are robust against a variety of combinations of elasticities. The article discusses effects both under autarky and free trade of both energy and green certificates. The results vary denpendent upon whether only one or a majority of actual countires introduces a domestic market or allows for international trade both in energy and the green certificate instrument.
Keywords: Q41; Q42; Q48; H23; H30; 330; Green certificates; energy market model; new instruments